Knowing Me, Knowing You. (December 2017) - Carr, Anna E.; Grand, Ann; Sullivan, Miriam
To engage effectively, it is important to understand audiences' values, attitudes, and background knowledge. Given that researchers are increasingly expected to be responsible for public engagement, we conducted a small study into their perceptions of publics' scientific knowledge. Our data show researchers feel public engagement is important and their particular field is not difficult to understand. However, our participants appeared to rely on guesswork when estimating public knowledge and to underestimate positive public attitudes toward science. We suggest if researchers develop a more accurate sense of audiences' knowledge and attitudes they will be able to engage more effectively and efficiently.